Visualisation of abnormal morphological development and molecular mechanisms that give rise to tracheo-oesophageal malformations and other VACTERL anomalies in an Adriamycin treated Mouse Model - Hajduk, Piotr (Trinity College (Dublin, Ireland). Department of Zoology, 2012)
Oesophageal atresia/Tracheo-oesophageal fistula (OA/TOF) are relatively common malfonnations of the foregut in humans (Spitz, 2007). They require urgent corrective surgery after birth and have an impact on the future health of the individual (Tomaselli el al., 2003). These abnormalities are mimicked by exposure of rat and mouse embryos in utero to the drug adriamycin. The causes of OA/TOF during human development are not known. However, a number of mouse mutants where different signalling pathways are directly affected, show similar abnormalities, implicating multiple and complex signalling mechanisms. The similarities in developmental outcome seen in human infants and in the Adriamycin Mouse Model (AMM) underline its use to unravel early embryological events and provide insight into our understanding of the disturbances that lead to such abnomialities. The objective of this thesis was to explore the morphological and molecular alterations in the AMM using a combination of 3D imaging Optical Projection Tomography (OPT) and molecular probes. Additionally, this thesis aimed to address the hypothesis that anomalies observed in the AMM could be a result of fundamental defects in the notochord leading to abnonnal delamination and ectopic placement of this potent signalling tissue during crucial stages of foregut development.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin